DETERMINING THE MORPHOLOGICAL CHARACTERISTICS OF FRANKFURTERS - M. Strateva; D. Stratev (Trakia Journal of Sciences, 2025)
PURPOSE: Processed meat products in the form of various sausages are very popular worldwide. One of the most widely consumed processed meat products are frankfurters. The aim of the study was to apply a histological method to differentiate various components in the composition of frankfurters by describing their morphological characteristics. METHODS: In this study, twenty-eight frankfurter samples from different brands were purchased from the retail network. RESULTS: The histological evaluation distinguished clearly muscle fibers. Some of the frankfurter samples had larger oval voids than others. The voids appeared empty of content and that gave them a porous or spongy appearance. Monovacuole white adipose tissue was observed in some of the frankfurter samples studied. The histological analysis also found the presence of tendons and cartilage. Fragments of skin, nerve and cells of plant origin were also identified. CONCLUSIONS: The histological method is a technique of practical importance for routine evaluation of the morphological composition of frankfurters.